5-Hydroxytryptamine 2A receptor antagonists as potential treatment for psychiatric disorders. (April 2013) - Mestre, Tiago A; Zurowski, Mateusz; Fox, Susan H
<x xml:space="preserve">Abstract</x> Introduction: 5-Hydroxytryptamine 2A receptors (5-HT2A-Rs) are widely expressed in the brain and have been implicated in mood and behavior. Based on the use of atypical antipsychotics in schizophrenia, antagonism of 5-HT2A-Rs initially emerged as a potential intervention capable of reducing the incidence of extrapyramidal symptoms, while exerting an effective antipsychotic action. More recently, highly selective 5-HT2A-R antagonists have been evaluated in the treatment of a wide range of other psychiatric disorders. Areas covered: The aim of the current review is to present important clinical studies investigating the potential therapeutic effects of 5-HT2A-R antagonists in both primary psychiatric disorders, such as schizophrenia and mood disorders, as well as in psychiatric manifestations of neurodegenerative disorders. We present an overview of 5-HT2A-Rs in normal brain function and the rationale for use in (neuro) psychiatric disease based on significant findings from genetic association studies, neuroimaging data and postmortem studies. The majority of the studies relate to schizophrenia, depression, anxiety, obsessive compulsive disorder and psychosis in Parkinson's disease and Alzheimer's disease. To date, there is sparse literature on 5-HT2A-Rs in Gilles de la Tourette syndrome, attention deficit hyperactivity disorder, eating disorders and autism spectrum disorders. The authors conclude by reviewing recent clinical trials investigating highly selective 5-HT2A-R antagonists in schizophrenia, psychosis in Parkinson's disease, insomnia and generalized anxiety. Expert opinion: Despite the potential, to date, 5-HT2A-R antagonists have not made an impact in the management of psychiatric disorders and psychiatric symptoms of neurodegenerative conditions.